STRATEGI PENGEMBANGAN KETERAMPILAN BAHASA INGGRIS MAHASISWA MENGGUNAKAN SELF-REGULATED LEARNING MELALUI DESAIN PEMBELAJARAN MODEL FLIPPED - Suherni, Suherni (LPPM Institut Pendidikan Nusantara Global, 2023)
This study examines the development of students' foreign language skills in learning English using the Flipped learning design which is designed with self-regulated learning strategies. The study was conducted using a quasi-experimental design. While the experimental group received learning strategies through a flipped classroom model designed with a self-regulated learning strategy, on the other hand the control class group received learning strategies that did not use the self-regulated learning strategy of the flipped learning class model. The results of the study show that the self-regulated learning strategy positively influences the development of foreign language skills in the flipped classroom model. A significant difference in support of groups working with the platform included self-learning strategies that excelled in speaking, reading, writing, and grammar test scores. However, based on the findings there is no significant difference in the results of the listening skill test. This Research also concludes that using strategies to help students be actively involved in activities outside and inside the classroom can contribute to improving their basic English skills.